Review on Utility of Antitoxic Preparations in Non-Poisonous conditions w.s.r. to Agadtantra - Anuja Vasant Nagrare1, Sonali Wairagade2, Tanvi Wairagade3, Anjali Chiwhane4 (Indian Journal of Forensic Medicine & Toxicology, 2020)
There are hundreds of formulations in the market, which are mostly prescribed by the physicians dependingupon their knowledge about the general context of reference. Analysis of the ingredients and the phalshrutiof each formulation give a clear picture about them and also help to make a better application in clinicalpractice. Nowadays, most of the diseases are caused due to unconventional etiology. When a disease is causedby unconventional etiology, it can be managed effectively by using principles of Agadtantra. Currently mostof the diseases require Nirvishikarana (Detoxification), for this reason Antitoxic formulations mentionedunder Ayurveda which contains singleantitoxicherb, combinationofanti-toxicherbs, herbs-mineralscombinations etc can be very effective insuch unknown etiology diseasedconditions. Antitoxic preparationswith Vishaharatwa(Antitoxic) property, as one of the action have a better effect in general diseases thanother formulation. This review article places of interest in the significant role of antitoxic formulationsmentioned in Agadtantra (Ayurvedic perspective of toxicology) to overcome diseases which are produceddue to unknown etiology.